Surface-hydrophobic core-shell structure composite moisture absorption hydrogel as well as preparation method and application thereof
Patent Information
- Application Number
- CN202411564391.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Existing composite hygroscopic hydrogels are prone to leakage of hygroscopic salt solutions in high humidity environments, resulting in a decrease in hygroscopic performance and poor long-term use stability.
The phase conversion method is used to build a porous hydrophobic polymer shell layer on the surface of the hydrogel to form a composite hygroscopic hydrogel of the nuclear shell structure to effectively prevent leakage of the hygroscopic salt solution.
It improves the long -term use of composite hygroscopic hydrogel and mechanical stability to ensure the high -efficiency and humidity absorption performance and cycle use of various humidity environments.
Smart Images

Figure CN119371684A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrophilic gel and air water extraction, and in particular, relates to a core-shell structure composite hygroscopic hydrogel with a hydrophobic surface, and a preparation method and application thereof. Background Art
[0002] Polymer hydrogel is a hydrophilic three-dimensional cross-linked network swollen by water molecules, and its network structure is formed by cross-linking polymer chains through covalent bonds or non-covalent bonds. Thanks to the good swelling properties of hydrogel, a large amount of water can be stored inside the hydrogel, and the evaporation enthalpy of water can be reduced to improve the desorption efficiency. Therefore, composite adsorbents with hydrogel as matrix material have received widespread attention and are likely to become the next generation of ideal adsorption-type air water extraction materials. Polymer hydrogels with hydrophilic networks and porous structures are regarded as ideal matrices for hygroscopic salt loading, because their porous structure can effectively prevent the aggregation of hygroscopic salts, thereby improving the long-term performance of hygroscopic salts.
[0003] Although the composite hygroscopic hydrogel can absorb a large amount of water vapor through the porous structure and high hydration capacity of the hydrogel, when the equilibrium adsorption capacity of the hydrogel exceeds its maximum water retention capacity, the hygroscopic salt solution will still leak from the hydrogel, causing the loss of hygroscopic salt, thereby leading to a decrease in the subsequent water vapor adsorption performance. Therefore, how to inhibit the leakage of hygroscopic salt while ensuring high hygroscopic capacity and thus improve the long-term stability of the composite hygroscopic hydrogel is still an urgent problem to be solved.
[0004] In this regard, researchers have constructed a photothermal hydrophobic shell layer on the surface of cellulose nanofiber aerogel through freeze-drying strategy to inhibit the leakage of hygroscopic salt solution. The photothermal hydrophobic shell layer is composed of polydimethylsiloxane, carbon black and cellulose nanofibers. The aerogel shows good long-term stability and rapid water vapor adsorption under high humidity. However, the preparation process of the polydimethylsiloxane shell layer is relatively cumbersome and not universal. In addition, the hydrophobic shell layer will inhibit the hygroscopic properties of the hydrogel to a certain extent. Therefore, it is of great significance to develop simpler physical or chemical means to construct a porous hydrophobic shell layer to inhibit the leakage of hygroscopic salt solution to improve the stability of the composite hygroscopic hydrogel for long-term use. Summary of the invention
[0005] In view of the defects of the prior art, the present invention provides a surface hydrophobic core-shell structure composite hygroscopic hydrogel and its preparation method and application, which solve the technical problems of hygroscopic salt leakage, poor water absorption performance of hygroscopic hydrogel, poor long-term use stability and complicated preparation method in the prior art.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a composite hygroscopic hydrogel with a core-shell structure and a hydrophobic surface is provided, which specifically comprises placing a hydrophilic gel loaded with a hygroscopic salt in a hydrophobic polymer solution, and using a phase inversion method to load a porous hydrophobic polymer shell layer on the surface of the hydrophilic gel, thereby obtaining a composite hygroscopic hydrogel with the hydrophilic gel loaded with a hygroscopic salt as a core layer and the porous hydrophobic polymer as a shell layer.
[0007] Preferably, the specific preparation steps of the hydrophilic gel loaded with hygroscopic salt are:
[0008] (1) preparing a hydrophilic gel precursor solution;
[0009] (2) heating or photocuring the gel precursor solution to obtain a hydrophilic gel;
[0010] (3) The hydrophilic gel is immersed in an aqueous solution of a hygroscopic salt to load the hygroscopic salt on the hydrophilic gel, thereby obtaining a hygroscopic salt-loaded hydrophilic gel.
[0011] Preferably, the hydrophilic gel is a polyzwitterionic electrolyte hydrogel, preferably one or more of polymethacryloylethyl sulfobetaine, polyvinyl alcohol, polyacrylic acid, sodium polystyrene sulfonate, polyacrylamide, and poly[2(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide.
[0012] Preferably, the hydrophilic gel described in step (2) is a microspherical hydrophilic gel, and its specific preparation steps are: dripping the hydrophilic gel precursor solution obtained in step (1) into the oily solution drop by drop, and then curing by heating or light curing to obtain the microspherical hydrophilic gel, wherein the diameter of the microspherical hydrophilic gel is 5 mm to 25 mm.
[0013] Preferably, the specific preparation steps of the hydrophobic polymer solution are: dissolving the hydrophobic polymer material in a mixture of a good solvent and a poor solvent to obtain a hydrophobic polymer solution;
[0014] Preferably, the hydrophobic polymer is one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, polypropylene, and polyacrylonitrile.
[0015] Preferably, the hygroscopic salt is one or more of potassium chloride, sodium chloride, potassium bromide, magnesium chloride, magnesium bromide, lithium chloride and lithium bromide.
[0016] Preferably, the concentration of hygroscopic salt in the hygroscopic salt solution is 1M-10M.
[0017] Preferably, the good solvent is one or more of methylene phenyl sulfone, N,N-dimethylformamide, and N-methylpyrrolidone, and the poor solvent is water.
[0018] Preferably, the volume ratio of the good solvent to the poor solvent is 0.01-0.06.
[0019] Preferably, in the hydrophobic polymer solution, the mass fraction of the hydrophobic polymer is 1% to 10%; the immersion time of the hydrophilic gel loaded with hygroscopic salt in the hydrophobic polymer solution is 3 to 10 minutes, the phase inversion temperature is 20°C to 80°C, and the thickness of the porous hydrophobic polymer shell is 200μm to 800μm.
[0020] According to another aspect of the present invention, a composite hygroscopic hydrogel prepared by the method for preparing the composite hygroscopic hydrogel with a core-shell structure having a hydrophobic surface is provided.
[0021] According to another aspect of the present invention, the application of the composite hygroscopic hydrogel is provided, which is applied to the fields of air water extraction, humidity control, and agricultural moisture retention.
[0022] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0023] (1) The hydrophilic / hydrophobic core-shell composite hygroscopic hydrogel of the present invention can achieve efficient adsorption of water vapor. The core-shell structure is composed of a hydrophilic gel core and a hydrophobic shell from the inside to the outside, wherein the hydrophilic gel core is responsible for capturing water vapor, while the hydrophobic shell effectively prevents the leakage of hygroscopic salt solution. In addition, the construction of the porous hydrophobic shell also enhances the mechanical stability of the hydrogel. This structural design ensures the material's efficient hygroscopic performance, long-term stability and recyclability under various humidity environments. At the same time, the structural design cleverly balances the high water absorption inside the hydrogel with the external moisture retention capacity, prolonging the service life of the material and providing a new strategy for the construction of hydrophilic gels. The composite hygroscopic hydrogel of the present invention exhibits excellent adsorption capacity under high humidity conditions.
[0024] (2) The present invention provides a simple preparation method, which uses a phase conversion method to construct a hydrophobic shell on the surface of the hydrogel. Rapid bidirectional diffusion of good solvent and poor solvent occurs on the surface of the hydrogel to form a relatively dense surface structure. Small droplets of a poor phase solution composed of a good solvent, a poor solvent, and a polymer are dispersed in a continuous polymer-rich phase and continue to grow until the surrounding rich phase solidifies to form a through-hole structure.
[0025] (3) The design of the core-shell structure of the present invention also allows the hygroscopic properties of the hydrogel to be regulated by changing the thickness and porosity of the shell layer, so that it can adapt to different environmental conditions and application requirements. The shell thickness can be regulated by changing the immersion time to achieve a porous hydrophobic polymer shell thickness of 200μm to 800μm, and the porosity can be regulated by the volume ratio of good solvent to poor solvent, curing temperature and shell material concentration. This size control capability provides flexibility for the applicability of hydrogels in different application scenarios. In applications that require a large amount of water vapor to be captured for multiple cycles, a hydrogel with a thicker shell layer can be selected to reduce the degree of hygroscopic salt leakage and increase the service life; and in environments that require rapid response or are space-constrained, a hydrogel with a thinner shell layer can be selected to increase the reaction speed and adaptability. The controllability of the core-shell size also helps to achieve large-scale production and processing of hydrogels, so that they can be customized according to market demand; the porous structure of the hydrophobic polymer shell layer can increase the amount of water vapor passing through and thus enhance the water vapor adsorption capacity of the core-shell composite hygroscopic hydrogel.
[0026] (4) The present invention uses hygroscopic salts. After being embedded in the hydrogel, the hygroscopic salts first capture water vapor and then liquefy water molecules in situ on the surface of the hydrogel. The liquefied water is transferred to the polymer network through the osmotic pressure difference and is stored due to the unique swelling properties of the hydrogel, thereby increasing the interaction between the gel and the water in the air and enhancing the adsorption capacity.
[0027] (5) The present invention uses microspherical hydrogel to obtain a hydrogel with the smallest surface area of the same volume. After being coated with a hydrophobic shell layer, the water vapor adsorption performance of the composite hygroscopic hydrogel will decrease. However, the use of a hydrophobic shell layer with a minimum surface area can make the inhibition effect surface smaller, thereby reducing the inhibitory effect of the subsequent hydrophobic shell layer on the water adsorption capacity.
[0028] (6) The present invention can select different types of gel precursor solutions as needed to meet different application requirements. The preparation process of the present invention does not require complicated post-processing steps, which not only simplifies the production process and reduces costs, but also is easy to scale up production, which is conducive to popularization and application. The simple preparation process only requires polymerization energy consumption, which overcomes the prior art that uses a grafting chemical method to fix the shell layer to the outside of the hydrogel core, which requires heating or light curing. It has no environmental impact and meets the requirements of green chemistry and sustainable production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the preparation of PSBMA-LiCl@PVDF;
[0030] Figure 2 Leakage test diagram of (a) PSBMA-LiCl and (b) PSBMA-LiCl@PVDF hygroscopic salt solution;
[0031] Figure 3 (a) equilibrium adsorption amount and (b) percentage of equilibrium adsorption amount during multiple cycles of PSBMA-LiCl and PSBMA-LiCl@PVDF;
[0032] Figure 4 Thermogravimetric curves of (a) PSBMA-LiCl and (b) PSBMA-LiCl@PVDF after different times of cyclic moisture absorption. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0034] The present invention provides a method for preparing a surface hydrophobic core-shell structure composite hygroscopic hydrogel, comprising the following steps:
[0035] (1) preparing a hydrophilic gel precursor solution;
[0036] (2) dripping the hydrophilic gel precursor solution into the oily solution drop by drop, and then heating or light curing to obtain a hydrophilic gel;
[0037] (3) Soaking the hydrophilic gel in an aqueous solution of a hygroscopic salt to load the hygroscopic salt on the hydrophilic gel, thereby obtaining a hygroscopic salt-loaded hydrophilic gel.
[0038] (4) dissolving the hydrophobic polymer material in a mixture of a good solvent and a poor solvent to obtain a hydrophobic polymer solution;
[0039] (5) Immersing the hydrophilic gel loaded with hygroscopic salt into the hydrophobic polymer solution, and then subjecting the solution to phase inversion, to obtain a composite hygroscopic hydrogel having the hydrophilic gel loaded with hygroscopic salt as a core layer and a porous hydrophobic polymer as a shell layer.
[0040] In some embodiments, the hydrophilic gel is a polyzwitterionic electrolyte hydrogel, preferably one or more of polymethacryloylethyl sulfobetaine, polyvinyl alcohol, polyacrylic acid, sodium polystyrene sulfonate, polyacrylamide, and poly[2(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide.
[0041] In some embodiments, the hydrophobic polymer is one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, polypropylene, and polyacrylonitrile.
[0042] In some embodiments, the hygroscopic salt is one or more of potassium chloride, sodium chloride, potassium bromide, magnesium chloride, magnesium bromide, lithium chloride, and lithium bromide.
[0043] In some embodiments, the concentration of the hygroscopic salt is 1M-10M.
[0044] In some embodiments, the good solvent is one or more of methylene phenyl sulfone, N,N-dimethylformamide, and N-methylpyrrolidone, the poor solvent is water, and the volume ratio of the good solvent to the poor solvent is 0.01-0.06.
[0045] In some embodiments, in the hydrophobic polymer solution, the mass fraction of the hydrophobic polymer is 1% to 10%;
[0046] In some embodiments, the immersion time of the hydrophilic gel loaded with hygroscopic salt in the hydrophobic polymer solution is 3 to 10 minutes, and the phase inversion temperature is 20° C. to 80° C.,
[0047] In some embodiments, the porous hydrophobic polymer shell layer has a thickness of 200 μm to 800 μm.
[0048] In some embodiments, the oily solution is one or more of methyl chloride, dichloromethane, and chlorobenzene.
[0049] In some embodiments, microfluidics, a needle, a pipette or a dropper are used to drop the gel precursor solution into the oily solution drop by drop.
[0050] Example 1
[0051] (1) 2.79 g of methyl methacryloylethyl sulfobetaine (SBMA) monomer and 15 mg of N,N′-methylenebisacrylamide (BIS) were dissolved in 5 mL of water to a monomer concentration of 2 M. 20 μL of photoinitiator 1173 was added and mixed evenly. The solution was poured into a plastic culture dish with a diameter of 35 mm and cured under ultraviolet light with a wavelength of 365 nm for 10 min. After that, the PSBMA hydrogel was fully immersed in water to wash away the unreacted reagent.
[0052] (2) The poly(methacryloylethylsulfobetaine) (PSBMA) hydrogel, which had been thoroughly washed with water, was immersed in an aqueous solution of 8 M LiCl for 12 h to load LiCl.
[0053] (3) The porous hydrophobic polyvinylidene fluoride (PVDF) shell layer was prepared by phase inversion method: 5% PVDF was dissolved in a mixed solution of dimethyl sulfoxide (DMSO) and water in a volume ratio of 5:95. The prepared PSBMA-LiCl hydrogel was immersed in the PVDF solution for 1 min to coat the surface with a layer of PVDF. Then, the PSBMA-LiCl hydrogel coated with PVDF was immersed in deionized water at 65°C for 10 min to perform solvent exchange to form the PVDF shell layer, thereby obtaining PSBMA-LiCl@PVDF. The preparation flow chart is shown in FIG. Figure 1 shown.
[0054] Example 2
[0055] The PSMBA in Example 1 was adjusted to polyacrylamide (PAM), poly[2(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (PSA), polyvinyl alcohol (PVA), polyacrylic acid (PAA), and sodium polystyrene sulfonate (PSS).
[0056] Example 3
[0057] The concentration of the LiCl solution in Example 1 was adjusted to 2M, 4M, 6M, and 10M.
[0058] Example 4
[0059] The aqueous solution of LiCl in Example 1 was adjusted to MgCl2, KCl, NaCl, and MgBr2.
[0060] Example 5
[0061] The PVDF in Example 1 was adjusted to polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), polypropylene (PP), and polyacrylonitrile (PAN).
[0062] Example 6
[0063] The mass fraction of PVDF in Example 1 was adjusted to 3%, 5%, and 10%.
[0064] Example 7
[0065] The DMSO and water in Example 1 were adjusted to N,N-dimethylformamide (DMF) and water.
[0066] Example 8
[0067] The volume ratio of DMSO to water in Example 1 was adjusted to 0.02, 0.03, and 0.04.
[0068] Example 9
[0069] The temperature of the cured shell layer in Example 1 was adjusted to 20°C, 40°C, and 60°C.
[0070] Comparative Example 1
[0071] (1) 2.79 g of methyl methacryloylethyl sulfobetaine (SBMA) monomer and 15 mg of N,N′-methylenebisacrylamide (BIS) were dissolved in 5 mL of water to a monomer concentration of 2 M. 20 μL of photoinitiator 1173 was added and mixed evenly. The solution was poured into a plastic culture dish with a diameter of 35 mm and cured under ultraviolet light with a wavelength of 365 nm for 10 min. After that, the PSBMA hydrogel was fully immersed in water to wash away the unreacted reagent.
[0072] (2) The poly(methacryloylethylsulfobetaine) (PSBMA) hydrogel, which had been thoroughly washed with water, was immersed in an aqueous solution of LiCl with a concentration of 8 M for 12 h to load LiCl and obtain PSBMA-LiCl.
[0073] Result analysis:
[0074] Figure 2 (a) is a PSBMA-LiCl hygroscopic salt solution leakage test diagram in comparative example 1, and (b) is a PSBMA-LiCl@PVDF hygroscopic salt solution leakage test diagram in example 1. Figure 2 As shown, at 4 h, neither the PSBMA-LiCl@PVDF hydrogel prepared in Example 1 nor the PSBMA-LiCl hydrogel prepared in Comparative Example 1 showed leakage of hygroscopic salt solution, while at 8 h, the PSBMA-LiCl hydrogel without PVDF coating had obvious leakage of hygroscopic salt solution; and the PSBMA-LiCl@PVDF hydrogel coated with PVDF did not show leakage of hygroscopic salt solution until 12 h. The above results indicate that PVDF coating has a significant effect on inhibiting the leakage of hygroscopic salt solution, and can reduce the leakage of hygroscopic salt solution by 100%.
[0075] Figure 3(a) is the equilibrium adsorption amount of PSBMA-LiCl and PSBMA-LiCl@PVDF during multiple cycles, and (b) is the percentage of equilibrium adsorption amount of PSBMA-LiCl and PSBMA-LiCl@PVDF during multiple cycles. The cyclic stability of the composite hygroscopic hydrogel before and after PVDF coating was studied under a relative humidity (RH) of 90%. Although the water vapor adsorption performance of the composite hygroscopic hydrogel will decrease after PVDF coating, the PVDF shell can inhibit the leakage of relative salt solution and prevent the composite hygroscopic hydrogel from experiencing a decline in water vapor adsorption performance due to a decrease in salt content under high humidity conditions. It still has obvious advantages during long-term use. Therefore, inhibiting the leakage of hygroscopic salt solution by coating PVDF is of great significance for the long-term use of the composite hygroscopic hydrogel in a high humidity environment.
[0076] Figure 4 (a) is the thermogravimetric curve of PSBMA-LiCl after 0, 1 and 5 cycles of adsorption. Figure 4 (b) is the thermogravimetric curve of PSBMA-LiCl@PVDF after 0, 1 and 5 cycles of adsorption. The weight loss test (TGA) showed that the PSBMA-LiCl hydrogel without PVDF coating showed a significant decrease in salt content after the first cycle, and its salt content decreased from 52% to 37%, and there was no further decrease after the fifth cycle. This is consistent with the observed leakage of hygroscopic salt solution. During the first water vapor adsorption process, the PSBMA-LiCl hydrogel showed obvious leakage of hygroscopic salt solution, while in the subsequent cycle experiments, the PSBMA-LiCl hydrogel did not leak hygroscopic salt solution. The PSBMA-LiCl@PVDF hydrogel coated with a hydrophobic PVDF shell did not show a decrease in salt content after five cycles. The above results further illustrate that the leakage of hygroscopic salt solution will lead to a decrease in the salt content inside the hydrogel, and the hydrophobic PVDF shell can effectively inhibit the leakage of hygroscopic salt solution, thereby ensuring that the salt content inside the composite hygroscopic hydrogel will not decrease during the process of water vapor adsorption, thereby improving the stability of the composite hygroscopic hydrogel during long-term use.
[0077] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a surface hydrophobic core-shell structure composite hygroscopic hydrogel, characterized in that: The hydrophilic gel loaded with hygroscopic salt is placed in a hydrophobic polymer solution, and a porous hydrophobic polymer shell layer is loaded on the surface of the hydrophilic gel by a phase inversion method, thereby obtaining a composite hygroscopic hydrogel with the hydrophilic gel loaded with hygroscopic salt as the core layer and the porous hydrophobic polymer as the shell layer.
2. The method for preparing a surface hydrophobic core-shell structure composite hygroscopic hydrogel according to claim 1, characterized in that: The specific preparation steps of the hydrophilic gel loaded with hygroscopic salt are as follows: (1) preparing a hydrophilic gel precursor solution; (2) heating or photocuring the gel precursor solution to obtain a hydrophilic gel; (3) The hydrophilic gel is immersed in an aqueous solution of a hygroscopic salt to load the hygroscopic salt on the hydrophilic gel, thereby obtaining a hygroscopic salt-loaded hydrophilic gel.
3. The method for preparing a surface hydrophobic core-shell structure composite hygroscopic hydrogel according to claim 2, characterized in that: The hydrophilic gel is a polyzwitterionic electrolyte hydrogel, preferably one or more of polymethacryloylethyl sulfobetaine, polyvinyl alcohol, polyacrylic acid, sodium polystyrene sulfonate, polyacrylamide, and poly[2(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide.
4. The method for preparing a surface hydrophobic core-shell structure composite hygroscopic hydrogel according to claim 3, characterized in that: The hydrophilic gel described in step (2) is a microspherical hydrophilic gel, and its specific preparation steps are: dripping the hydrophilic gel precursor solution obtained in step (1) into the oily solution drop by drop, and then curing by heating or light curing to obtain the microspherical hydrophilic gel, wherein the diameter of the microspherical hydrophilic gel is 5mm to 25mm.
5. The method for preparing a surface hydrophobic core-shell structure composite hygroscopic hydrogel according to claim 4, characterized in that: The specific preparation steps of the hydrophobic polymer solution are: dissolving the hydrophobic polymer material in a mixture of a good solvent and a poor solvent to obtain the hydrophobic polymer solution.
6. The method for preparing a surface hydrophobic core-shell structure composite hygroscopic hydrogel according to claim 5, characterized in that: The hydrophobic polymer is one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, polypropylene, and polyacrylonitrile; the hygroscopic salt is one or more of potassium chloride, sodium chloride, potassium bromide, magnesium chloride, magnesium bromide, lithium chloride, and lithium bromide; and the concentration of the hygroscopic salt in the hygroscopic salt solution is 1 mol / L-10 mol / L.
7. The method for preparing a surface hydrophobic core-shell structure composite hygroscopic hydrogel according to claim 5, characterized in that: The good solvent is one or more of methylene phenyl sulfone, N,N-dimethylformamide, N-methyl pyrrolidone, and dimethyl sulfoxide; the poor solvent is water; and the volume ratio of the good solvent to the poor solvent is 0.01-0.
06.
8. The method for preparing a surface hydrophobic core-shell structure composite hygroscopic hydrogel according to claim 7, characterized in that: In the hydrophobic polymer solution, the mass fraction of the hydrophobic polymer is 1% to 10%; the immersion time of the hydrophilic gel loaded with hygroscopic salt in the hydrophobic polymer solution is 3 to 10 minutes, the phase inversion temperature is 20° C. to 80° C., and the thickness of the porous hydrophobic polymer shell layer is 200 μm to 800 μm.
9. The composite hygroscopic hydrogel prepared according to the method for preparing a composite hygroscopic hydrogel with a core-shell structure and having a hydrophobic surface according to any one of claims 1 to 8.
10. The use of the composite hygroscopic hydrogel according to claim 9, characterized in that: It is used in the fields of air water extraction, humidity control, and agricultural moisturizing.
Citation Information
Patent Citations
Method for preparing meshed PVDF (polyvinylidene fluoride) film based on PVA (polyvinyl alcohol) gel
CN105126648A
Self-hygroscopic hydrogel, preparation method and thermal management method based on self-hygroscopic hydrogel
CN109943002A
Preparation method of core-shell structure PAA-PNIPAAm hydrogel material for environmental water collection
CN114940799A
Stable moisture absorption photo-thermal core-shell aerogel material and preparation method and application thereof
CN117164962A
Anisotropic super-hydrophobic / super-oleophylic composite aerogel material and preparation method thereof
CN117447764A
Cited By
Bionic polymeric gel as well as preparation method and application thereof
CN120904621A
Porous composite gel as well as preparation method and application thereof in atmospheric catchment
CN121005949A
Preparation method of stainless steel mesh based on hydrophilic-hydrophobic hybrid coating and application of stainless steel mesh in taking water from air
CN121911161A
Hydrogel with directional conical porous structure and preparation method thereof
CN122103664A
Hydrogel with directional conical porous structure and preparation method thereof
CN122103664B